BREASTFEEDING MOTHER’S KNOWLEDGE OF NEONATAL HYGIENE AT MUKONO GENERAL HOSPITAL IN MUKONO MUNICIPALITY: A CROSS-SECTIONAL STUDY. - Kakooza, Abdul wahabu; Kyomugisha, Hope; Lamwaka , Melat Linda; Nakato, Agnes Anita (Student’s Journal of Health Research Africa, 2024)
Background Knowledge refers to the information, breastfeeding mothers have on how and when to clean breast-feeding bottles, the breast during the breast-feeding process, the neonates and their clothing, and how to keep the neonate’s surroundings. The study aims to describe the knowledge of breastfeeding mothers on the hygiene of their neonates. Methodology A quantitative descriptive cross-sectional study involving only breast-feeding mothers with babies less than 28 days of life, both those who have gone through normal delivery and caesarian section irrespective of their age, tribe, and education level. Data was analyzed using SPSS version 24.0. A simple random method was used to select 296 respondents. Results 93.3% (28/30) of the respondents managed to at least attend one or more than one level of education. 70.0 % (21/30) of the mothers were assisted by midwives, 10.0% (3/30) were assisted by doctors, 6.7% (2/30) were assisted by traditional birth attendants, and 13.3% (4/30) were assisted by other people in the community while delivering their current babies. About 53.3 % (16/30) of the mothers knew that the baby’s cord should be cleaned with saline water, 40.0% reported bathing their neonates with soapy water and dry, majority 56.7% (12/30) knew that the mother’s breast should first be wiped before breastfeeding. Concerning the prevention of diseases in babies, 53.3% of mothers reported that it is important to dry the baby after bathing. Conclusion The majority of the respondents had the right knowledge about Neonatal hygiene but the proportion of those who did not have relevant adequate knowledge is a threat to the general health of the children Recommendations Health workers need to bridge the gap between the community and health workers to encourage mothers to seek healthcare freely without fear.